2019
DOI: 10.3390/coatings9090548
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of Multiple Solutions for Caputo Fractional-Order-Two Dimensional Magnetohydrodynamic Unsteady Flow of Generalized Viscous Fluid over a Shrinking Sheet Using the Adams-Type Predictor-Corrector Method

Abstract: In this paper, magnetohydrodynamic (MHD) flow over a shrinking sheet and heat transfer with viscous dissipation has been studied. The governing equations of the considered problem are transformed into ordinary differential equations using similarity transformation. The resultant equations are converted into a system of fractional differential boundary layer equations by employing a Caputo derivative which is then solved numerically using the Adams-type predictor-corrector method (APCM). The results show the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(41 reference statements)
0
11
0
Order By: Relevance
“…Their remarkable result was that the velocity field can be expressed as an upraising function of the electric field and unsteadiness parameter whereas the temperature distribution as the Biot number and radiation parameter. MHD micropolar fluid flows over an exponentially shrinking sheet were simulated by Lund et al [17][18][19] considering different boundary conditions and solution procedures to investigate the stability of the different solutions. In all studies, they concluded that only the first solution is stable.…”
mentioning
confidence: 99%
“…Their remarkable result was that the velocity field can be expressed as an upraising function of the electric field and unsteadiness parameter whereas the temperature distribution as the Biot number and radiation parameter. MHD micropolar fluid flows over an exponentially shrinking sheet were simulated by Lund et al [17][18][19] considering different boundary conditions and solution procedures to investigate the stability of the different solutions. In all studies, they concluded that only the first solution is stable.…”
mentioning
confidence: 99%
“…The magnetohydrodynamic flow over a shrinking sheet and heat transfer with viscous dissipation has been studied in [15]. The governing equations of the considered problem are transformed into ordinary differential equations while using similarity transformation.…”
Section: Methodologies and Usagesmentioning
confidence: 99%
“…The KDV equation used to model long waves, tides, solitary waves, and wave propagating in a shallow canal. A partial differential Kortewege-De Vries equation of third order is also applied to study the non-linear model of water waves in superficial canal certain namely canal [3], in the time when wave in water was of important concentration in applications in navigational design and also for the awareness of flood and tides [4,5]. The applications in numerous areas of physics, applied science and other scientific applications, therefore the excessive amount of investigation as a research work has been capitalized in the study of KDV equations [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%